refactor(library/data/list): avoid placeholders '_', make first argument of false_elim implicit
Signed-off-by: Leonardo de Moura <leonardo@microsoft.com>
This commit is contained in:
parent
aace5c37cd
commit
8dec18018c
9 changed files with 84 additions and 86 deletions
|
@ -11,15 +11,15 @@
|
|||
|
||||
import tools.tactic
|
||||
import data.nat
|
||||
import logic
|
||||
import logic tools.helper_tactics
|
||||
-- import if -- for find
|
||||
|
||||
using nat
|
||||
using eq_ops
|
||||
using helper_tactics
|
||||
|
||||
namespace list
|
||||
|
||||
|
||||
-- Type
|
||||
-- ----
|
||||
|
||||
|
@ -52,24 +52,23 @@ list_rec t (fun x : T, fun l : list T, fun u : list T, cons x u) s
|
|||
|
||||
infixl `++` : 65 := concat
|
||||
|
||||
theorem nil_concat (t : list T) : nil ++ t = t := refl _
|
||||
theorem nil_concat {t : list T} : nil ++ t = t
|
||||
|
||||
theorem cons_concat (x : T) (s t : list T) : (x :: s) ++ t = x :: (s ++ t) := refl _
|
||||
theorem cons_concat {x : T} {s t : list T} : (x :: s) ++ t = x :: (s ++ t)
|
||||
|
||||
theorem concat_nil (t : list T) : t ++ nil = t :=
|
||||
list_induction_on t (refl _)
|
||||
theorem concat_nil {t : list T} : t ++ nil = t :=
|
||||
list_induction_on t rfl
|
||||
(take (x : T) (l : list T) (H : concat l nil = l),
|
||||
show concat (cons x l) nil = cons x l, from H ▸ refl _)
|
||||
show concat (cons x l) nil = cons x l, from H ▸ rfl)
|
||||
|
||||
theorem concat_assoc (s t u : list T) : s ++ t ++ u = s ++ (t ++ u) :=
|
||||
list_induction_on s (refl _)
|
||||
theorem concat_assoc {s t u : list T} : s ++ t ++ u = s ++ (t ++ u) :=
|
||||
list_induction_on s rfl
|
||||
(take x l,
|
||||
assume H : concat (concat l t) u = concat l (concat t u),
|
||||
calc
|
||||
concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : refl _
|
||||
... = cons x (concat l (concat t u)) : { H }
|
||||
... = concat (cons x l) (concat t u) : refl _)
|
||||
|
||||
concat (concat (cons x l) t) u = cons x (concat (concat l t) u) : rfl
|
||||
... = cons x (concat l (concat t u)) : {H}
|
||||
... = concat (cons x l) (concat t u) : rfl)
|
||||
|
||||
-- Length
|
||||
-- ------
|
||||
|
@ -78,9 +77,9 @@ definition length : list T → ℕ := list_rec 0 (fun x l m, succ m)
|
|||
|
||||
theorem length_nil : length (@nil T) = 0 := rfl
|
||||
|
||||
theorem length_cons (x : T) (t : list T) : length (x :: t) = succ (length t) := rfl
|
||||
theorem length_cons {x : T} {t : list T} : length (x :: t) = succ (length t)
|
||||
|
||||
theorem length_concat (s t : list T) : length (s ++ t) = length s + length t :=
|
||||
theorem length_concat {s t : list T} : length (s ++ t) = length s + length t :=
|
||||
list_induction_on s
|
||||
(calc
|
||||
length (concat nil t) = length t : rfl
|
||||
|
@ -90,99 +89,95 @@ list_induction_on s
|
|||
assume H : length (concat s t) = length s + length t,
|
||||
calc
|
||||
length (concat (cons x s) t ) = succ (length (concat s t)) : rfl
|
||||
... = succ (length s + length t) : { H }
|
||||
... = succ (length s + length t) : {H}
|
||||
... = succ (length s) + length t : {add_succ_left⁻¹}
|
||||
... = length (cons x s) + length t : rfl)
|
||||
|
||||
-- add_rewrite length_nil length_cons
|
||||
|
||||
|
||||
-- Append
|
||||
-- ------
|
||||
|
||||
definition append (x : T) : list T → list T := list_rec [x] (fun y l l', y :: l')
|
||||
|
||||
theorem append_nil (x : T) : append x nil = [x] := refl _
|
||||
theorem append_nil {x : T} : append x nil = [x]
|
||||
|
||||
theorem append_cons (x : T) (y : T) (l : list T) : append x (y :: l) = y :: (append x l) := refl _
|
||||
theorem append_cons {x y : T} {l : list T} : append x (y :: l) = y :: (append x l)
|
||||
|
||||
theorem append_eq_concat (x : T) (l : list T) : append x l = l ++ [x] := refl _
|
||||
theorem append_eq_concat {x : T} {l : list T} : append x l = l ++ [x]
|
||||
|
||||
-- add_rewrite append_nil append_cons
|
||||
|
||||
|
||||
-- Reverse
|
||||
-- -------
|
||||
|
||||
definition reverse : list T → list T := list_rec nil (fun x l r, r ++ [x])
|
||||
|
||||
theorem reverse_nil : reverse (@nil T) = nil := refl _
|
||||
theorem reverse_nil : reverse (@nil T) = nil
|
||||
|
||||
theorem reverse_cons (x : T) (l : list T) : reverse (x :: l) = append x (reverse l) := refl _
|
||||
theorem reverse_cons {x : T} {l : list T} : reverse (x :: l) = append x (reverse l)
|
||||
|
||||
theorem reverse_singleton (x : T) : reverse [x] = [x] := refl _
|
||||
theorem reverse_singleton {x : T} : reverse [x] = [x]
|
||||
|
||||
theorem reverse_concat (s t : list T) : reverse (s ++ t) = (reverse t) ++ (reverse s) :=
|
||||
list_induction_on s (symm (concat_nil _))
|
||||
theorem reverse_concat {s t : list T} : reverse (s ++ t) = (reverse t) ++ (reverse s) :=
|
||||
list_induction_on s (concat_nil⁻¹)
|
||||
(take x s,
|
||||
assume IH : reverse (s ++ t) = concat (reverse t) (reverse s),
|
||||
calc
|
||||
reverse ((x :: s) ++ t) = reverse (s ++ t) ++ [x] : refl _
|
||||
... = reverse t ++ reverse s ++ [x] : {IH}
|
||||
... = reverse t ++ (reverse s ++ [x]) : concat_assoc _ _ _
|
||||
... = reverse t ++ (reverse (x :: s)) : refl _)
|
||||
reverse ((x :: s) ++ t) = reverse (s ++ t) ++ [x] : rfl
|
||||
... = reverse t ++ reverse s ++ [x] : {IH}
|
||||
... = reverse t ++ (reverse s ++ [x]) : concat_assoc
|
||||
... = reverse t ++ (reverse (x :: s)) : rfl)
|
||||
|
||||
theorem reverse_reverse (l : list T) : reverse (reverse l) = l :=
|
||||
list_induction_on l (refl _)
|
||||
theorem reverse_reverse {l : list T} : reverse (reverse l) = l :=
|
||||
list_induction_on l rfl
|
||||
(take x l',
|
||||
assume H: reverse (reverse l') = l',
|
||||
show reverse (reverse (x :: l')) = x :: l', from
|
||||
calc
|
||||
reverse (reverse (x :: l')) = reverse (reverse l' ++ [x]) : refl _
|
||||
... = reverse [x] ++ reverse (reverse l') : reverse_concat _ _
|
||||
... = [x] ++ l' : { H }
|
||||
... = x :: l' : refl _)
|
||||
reverse (reverse (x :: l')) = reverse (reverse l' ++ [x]) : rfl
|
||||
... = reverse [x] ++ reverse (reverse l') : reverse_concat
|
||||
... = [x] ++ l' : {H}
|
||||
... = x :: l' : rfl)
|
||||
|
||||
theorem append_eq_reverse_cons (x : T) (l : list T) : append x l = reverse (x :: reverse l) :=
|
||||
list_induction_on l (refl _)
|
||||
theorem append_eq_reverse_cons {x : T} {l : list T} : append x l = reverse (x :: reverse l) :=
|
||||
list_induction_on l rfl
|
||||
(take y l',
|
||||
assume H : append x l' = reverse (x :: reverse l'),
|
||||
calc
|
||||
append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat _ _
|
||||
... = concat (reverse (reverse (y :: l'))) [ x ] : {symm (reverse_reverse _)}
|
||||
... = reverse (x :: (reverse (y :: l'))) : refl _)
|
||||
append x (y :: l') = (y :: l') ++ [ x ] : append_eq_concat
|
||||
... = concat (reverse (reverse (y :: l'))) [ x ] : {reverse_reverse⁻¹}
|
||||
... = reverse (x :: (reverse (y :: l'))) : rfl)
|
||||
|
||||
|
||||
-- Head and tail
|
||||
-- -------------
|
||||
|
||||
definition head (x0 : T) : list T → T := list_rec x0 (fun x l h, x)
|
||||
definition head (x : T) : list T → T := list_rec x (fun x l h, x)
|
||||
|
||||
theorem head_nil (x0 : T) : head x0 (@nil T) = x0 := refl _
|
||||
theorem head_nil {x : T} : head x (@nil T) = x
|
||||
|
||||
theorem head_cons (x : T) (x0 : T) (t : list T) : head x0 (x :: t) = x := refl _
|
||||
theorem head_cons {x x' : T} {t : list T} : head x' (x :: t) = x
|
||||
|
||||
theorem head_concat (s t : list T) (x0 : T) : s ≠ nil → (head x0 (s ++ t) = head x0 s) :=
|
||||
theorem head_concat {s t : list T} {x : T} : s ≠ nil → (head x (s ++ t) = head x s) :=
|
||||
list_cases_on s
|
||||
(take H : nil ≠ nil, absurd (refl nil) H)
|
||||
(take x s,
|
||||
take H : cons x s ≠ nil,
|
||||
(take H : nil ≠ nil, absurd rfl H)
|
||||
(take x s, take H : cons x s ≠ nil,
|
||||
calc
|
||||
head x0 (concat (cons x s) t) = head x0 (cons x (concat s t)) : {cons_concat _ _ _}
|
||||
... = x : {head_cons _ _ _}
|
||||
... = head x0 (cons x s) : {symm ( head_cons x x0 s)})
|
||||
head x (concat (cons x s) t) = head x (cons x (concat s t)) : {cons_concat}
|
||||
... = x : {head_cons}
|
||||
... = head x (cons x s) : {head_cons⁻¹})
|
||||
|
||||
definition tail : list T → list T := list_rec nil (fun x l b, l)
|
||||
|
||||
theorem tail_nil : tail (@nil T) = nil := refl _
|
||||
theorem tail_nil : tail (@nil T) = nil
|
||||
|
||||
theorem tail_cons (x : T) (l : list T) : tail (cons x l) = l := refl _
|
||||
theorem tail_cons {x : T} {l : list T} : tail (cons x l) = l
|
||||
|
||||
theorem cons_head_tail (x0 : T) (l : list T) : l ≠ nil → (head x0 l) :: (tail l) = l :=
|
||||
theorem cons_head_tail {x : T} {l : list T} : l ≠ nil → (head x l) :: (tail l) = l :=
|
||||
list_cases_on l
|
||||
(assume H : nil ≠ nil, absurd (refl _) H)
|
||||
(take x l, assume H : cons x l ≠ nil, refl _)
|
||||
|
||||
(assume H : nil ≠ nil, absurd rfl H)
|
||||
(take x l, assume H : cons x l ≠ nil, rfl)
|
||||
|
||||
-- List membership
|
||||
-- ---------------
|
||||
|
@ -192,11 +187,11 @@ definition mem (x : T) : list T → Prop := list_rec false (fun y l H, x = y ∨
|
|||
infix `∈` := mem
|
||||
|
||||
-- TODO: constructively, equality is stronger. Use that?
|
||||
theorem mem_nil (x : T) : x ∈ nil ↔ false := iff_refl _
|
||||
theorem mem_nil {x : T} : x ∈ nil ↔ false := iff_rfl
|
||||
|
||||
theorem mem_cons (x : T) (y : T) (l : list T) : mem x (cons y l) ↔ (x = y ∨ mem x l) := iff_refl _
|
||||
theorem mem_cons {x y : T} {l : list T} : mem x (cons y l) ↔ (x = y ∨ mem x l) := iff_rfl
|
||||
|
||||
theorem mem_concat_imp_or (x : T) (s t : list T) : x ∈ s ++ t → x ∈ s ∨ x ∈ t :=
|
||||
theorem mem_concat_imp_or {x : T} {s t : list T} : x ∈ s ++ t → x ∈ s ∨ x ∈ t :=
|
||||
list_induction_on s or_inr
|
||||
(take y s,
|
||||
assume IH : x ∈ s ++ t → x ∈ s ∨ x ∈ t,
|
||||
|
@ -205,9 +200,9 @@ list_induction_on s or_inr
|
|||
have H3 : x = y ∨ x ∈ s ∨ x ∈ t, from or_imp_or_right H2 IH,
|
||||
iff_elim_right or_assoc H3)
|
||||
|
||||
theorem mem_or_imp_concat (x : T) (s t : list T) : x ∈ s ∨ x ∈ t → x ∈ s ++ t :=
|
||||
theorem mem_or_imp_concat {x : T} {s t : list T} : x ∈ s ∨ x ∈ t → x ∈ s ++ t :=
|
||||
list_induction_on s
|
||||
(take H, or_elim H (false_elim _) (assume H, H))
|
||||
(take H, or_elim H false_elim (assume H, H))
|
||||
(take y s,
|
||||
assume IH : x ∈ s ∨ x ∈ t → x ∈ s ++ t,
|
||||
assume H : x ∈ y :: s ∨ x ∈ t,
|
||||
|
@ -218,24 +213,24 @@ list_induction_on s
|
|||
(take H2 : x ∈ s, or_inr (IH (or_inl H2))))
|
||||
(assume H1 : x ∈ t, or_inr (IH (or_inr H1))))
|
||||
|
||||
theorem mem_concat (x : T) (s t : list T) : x ∈ s ++ t ↔ x ∈ s ∨ x ∈ t
|
||||
:= iff_intro (mem_concat_imp_or _ _ _) (mem_or_imp_concat _ _ _)
|
||||
theorem mem_concat {x : T} {s t : list T} : x ∈ s ++ t ↔ x ∈ s ∨ x ∈ t
|
||||
:= iff_intro mem_concat_imp_or mem_or_imp_concat
|
||||
|
||||
theorem mem_split (x : T) (l : list T) : x ∈ l → ∃s t : list T, l = s ++ (x :: t) :=
|
||||
theorem mem_split {x : T} {l : list T} : x ∈ l → ∃s t : list T, l = s ++ (x :: t) :=
|
||||
list_induction_on l
|
||||
(take H : x ∈ nil, false_elim _ (iff_elim_left (mem_nil x) H))
|
||||
(take H : x ∈ nil, false_elim (iff_elim_left mem_nil H))
|
||||
(take y l,
|
||||
assume IH : x ∈ l → ∃s t : list T, l = s ++ (x :: t),
|
||||
assume H : x ∈ y :: l,
|
||||
or_elim H
|
||||
(assume H1 : x = y,
|
||||
exists_intro nil
|
||||
(exists_intro l (subst H1 (refl _))))
|
||||
(exists_intro l (subst H1 rfl)))
|
||||
(assume H1 : x ∈ l,
|
||||
obtain s (H2 : ∃t : list T, l = s ++ (x :: t)), from IH H1,
|
||||
obtain t (H3 : l = s ++ (x :: t)), from H2,
|
||||
have H4 : y :: l = (y :: s) ++ (x :: t),
|
||||
from subst H3 (refl (y :: l)),
|
||||
from subst H3 rfl,
|
||||
exists_intro _ (exists_intro _ H4)))
|
||||
|
||||
-- Find
|
||||
|
@ -276,12 +271,12 @@ list_induction_on l
|
|||
-- nth element
|
||||
-- -----------
|
||||
|
||||
definition nth (x0 : T) (l : list T) (n : ℕ) : T :=
|
||||
nat_rec (λl, head x0 l) (λm f l, f (tail l)) n l
|
||||
definition nth (x : T) (l : list T) (n : ℕ) : T :=
|
||||
nat_rec (λl, head x l) (λm f l, f (tail l)) n l
|
||||
|
||||
theorem nth_zero (x0 : T) (l : list T) : nth x0 l 0 = head x0 l := refl _
|
||||
theorem nth_zero {x : T} {l : list T} : nth x l 0 = head x l
|
||||
|
||||
theorem nth_succ (x0 : T) (l : list T) (n : ℕ) : nth x0 l (succ n) = nth x0 (tail l) n := refl _
|
||||
theorem nth_succ {x : T} {l : list T} {n : ℕ} : nth x l (succ n) = nth x (tail l) n
|
||||
|
||||
end
|
||||
|
||||
|
|
|
@ -28,7 +28,7 @@ section
|
|||
sigma_rec H p
|
||||
|
||||
theorem dpair_ext (p : sigma B) : dpair (dpr1 p) (dpr2 p) = p :=
|
||||
sigma_destruct p (take a b, refl _)
|
||||
sigma_destruct p (take a b, rfl)
|
||||
|
||||
-- Note that we give the general statment explicitly, to help the unifier
|
||||
theorem dpair_eq {a1 a2 : A} {b1 : B a1} {b2 : B a2} (H1 : a1 = a2) (H2 : eq_rec_on H1 b1 = b2) :
|
||||
|
|
|
@ -71,13 +71,13 @@ rec_on s1
|
|||
(take a2, show decidable (inl B a1 = inl B a2), from H1 a1 a2)
|
||||
(take b2,
|
||||
have H3 : (inl B a1 = inr A b2) ↔ false,
|
||||
from iff_intro inl_neq_inr (assume H4, false_elim _ H4),
|
||||
from iff_intro inl_neq_inr (assume H4, false_elim H4),
|
||||
show decidable (inl B a1 = inr A b2), from decidable_iff_equiv _ (iff_symm H3)))
|
||||
(take b1, show decidable (inr A b1 = s2), from
|
||||
rec_on s2
|
||||
(take a2,
|
||||
have H3 : (inr A b1 = inl B a2) ↔ false,
|
||||
from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim _ H4),
|
||||
from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim H4),
|
||||
show decidable (inr A b1 = inl B a2), from decidable_iff_equiv _ (iff_symm H3))
|
||||
(take b2, show decidable (inr A b1 = inr A b2), from H2 b1 b2))
|
||||
|
||||
|
|
|
@ -16,6 +16,9 @@ notation `⋆`:max := star
|
|||
theorem unit_eq (a b : unit) : a = b :=
|
||||
unit_rec (unit_rec (refl ⋆) b) a
|
||||
|
||||
theorem unit_eq_star (a : unit) : a = star :=
|
||||
unit_eq a star
|
||||
|
||||
theorem unit_inhabited [instance] : inhabited unit :=
|
||||
inhabited_mk ⋆
|
||||
|
||||
|
|
|
@ -35,9 +35,9 @@ theorem propext {a b : Prop} (Hab : a → b) (Hba : b → a) : a = b :=
|
|||
or_elim (prop_complete a)
|
||||
(assume Hat, or_elim (prop_complete b)
|
||||
(assume Hbt, Hat ⬝ Hbt⁻¹)
|
||||
(assume Hbf, false_elim (a = b) (Hbf ▸ (Hab (eq_true_elim Hat)))))
|
||||
(assume Hbf, false_elim (Hbf ▸ (Hab (eq_true_elim Hat)))))
|
||||
(assume Haf, or_elim (prop_complete b)
|
||||
(assume Hbt, false_elim (a = b) (Haf ▸ (Hba (eq_true_elim Hbt))))
|
||||
(assume Hbt, false_elim (Haf ▸ (Hba (eq_true_elim Hbt))))
|
||||
(assume Hbf, Haf ⬝ Hbf⁻¹))
|
||||
|
||||
theorem iff_to_eq {a b : Prop} (H : a ↔ b) : a = b :=
|
||||
|
|
|
@ -44,7 +44,7 @@ or_elim (em a) (assume Ha, Hab Ha) (assume Hna, Hnab Hna)
|
|||
theorem by_contradiction {p : Prop} {Hp : decidable p} (H : ¬p → false) : p :=
|
||||
or_elim (em p)
|
||||
(assume H1 : p, H1)
|
||||
(assume H1 : ¬p, false_elim p (H H1))
|
||||
(assume H1 : ¬p, false_elim (H H1))
|
||||
|
||||
theorem and_decidable [instance] {a b : Prop} (Ha : decidable a) (Hb : decidable b) :
|
||||
decidable (a ∧ b) :=
|
||||
|
|
|
@ -47,7 +47,7 @@ theorem not_not_elim {a : Prop} {D : decidable a} (H : ¬¬a) : a :=
|
|||
iff_mp not_not_iff H
|
||||
|
||||
theorem not_true : (¬true) ↔ false :=
|
||||
iff_intro (assume H, H trivial) (false_elim _)
|
||||
iff_intro (assume H, H trivial) false_elim
|
||||
|
||||
theorem not_false : (¬false) ↔ true :=
|
||||
iff_intro (assume H, trivial) (assume H H', H')
|
||||
|
@ -117,12 +117,12 @@ iff_intro
|
|||
theorem iff_false_intro {a : Prop} (H : ¬a) : a ↔ false :=
|
||||
iff_intro
|
||||
(assume H1 : a, absurd H1 H)
|
||||
(assume H2 : false, false_elim a H2)
|
||||
(assume H2 : false, false_elim H2)
|
||||
|
||||
theorem a_neq_a {A : Type} (a : A) : (a ≠ a) ↔ false :=
|
||||
iff_intro
|
||||
(assume H, a_neq_a_elim H)
|
||||
(assume H, false_elim (a ≠ a) H)
|
||||
(assume H, false_elim H)
|
||||
|
||||
theorem eq_id {A : Type} (a : A) : (a = a) ↔ true :=
|
||||
iff_true_intro (refl a)
|
||||
|
@ -135,7 +135,7 @@ iff_intro
|
|||
(assume H,
|
||||
have H' : ¬a, from assume Ha, (H ▸ Ha) Ha,
|
||||
H' (H⁻¹ ▸ H'))
|
||||
(assume H, false_elim (a ↔ ¬a) H)
|
||||
(assume H, false_elim H)
|
||||
|
||||
theorem true_eq_false : (true ↔ false) ↔ false :=
|
||||
not_true ▸ (a_iff_not_a true)
|
||||
|
|
|
@ -18,7 +18,7 @@ abbreviation imp (a b : Prop) : Prop := a → b
|
|||
|
||||
inductive false : Prop
|
||||
|
||||
theorem false_elim (c : Prop) (H : false) : c :=
|
||||
theorem false_elim {c : Prop} (H : false) : c :=
|
||||
false_rec c H
|
||||
|
||||
inductive true : Prop :=
|
||||
|
@ -36,7 +36,7 @@ theorem not_intro {a : Prop} (H : a → false) : ¬a := H
|
|||
theorem not_elim {a : Prop} (H1 : ¬a) (H2 : a) : false := H1 H2
|
||||
|
||||
theorem absurd {a : Prop} {b : Prop} (H1 : a) (H2 : ¬a) : b :=
|
||||
false_elim b (H2 H1)
|
||||
false_elim (H2 H1)
|
||||
|
||||
theorem not_not_intro {a : Prop} (Ha : a) : ¬¬a :=
|
||||
assume Hna : ¬a, absurd Ha Hna
|
||||
|
|
|
@ -57,13 +57,13 @@ rec_on s1
|
|||
(take a2, show decidable (inl B a1 = inl B a2), from H1 a1 a2)
|
||||
(take b2,
|
||||
have H3 : (inl B a1 = inr A b2) ↔ false,
|
||||
from iff_intro inl_neq_inr (assume H4, false_elim _ H4),
|
||||
from iff_intro inl_neq_inr (assume H4, false_elim H4),
|
||||
show decidable (inl B a1 = inr A b2), from decidable_iff_equiv _ (iff_symm H3)))
|
||||
(take b1, show decidable (inr A b1 = s2), from
|
||||
rec_on s2
|
||||
(take a2,
|
||||
have H3 : (inr A b1 = inl B a2) ↔ false,
|
||||
from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim _ H4),
|
||||
from iff_intro (assume H4, inl_neq_inr (symm H4)) (assume H4, false_elim H4),
|
||||
show decidable (inr A b1 = inl B a2), from decidable_iff_equiv _ (iff_symm H3))
|
||||
(take b2, show decidable (inr A b1 = inr A b2), from H2 b1 b2))
|
||||
|
||||
|
|
Loading…
Reference in a new issue